Clinical presentation and management outcomes of pediatric lung abscess: A retrospective cohort study - Lina Alshadfan; Saleh Abualhaj; Muna Kilani; Hisham Hamdan; Diana AlSaify; Samia Saber Abu Taleb; Mohammed K. Al-raqad (PLoS ONE, 2026)
Background Pediatric lung abscess is an uncommon but potentially serious complication of pneumonia. Limited data exists on its clinical features, diagnostic workup, and outcomes in otherwise healthy children. Objective To describe the clinical characteristics, management strategies, and outcomes of children diagnosed and treated for lung abscess in Jordan. Methods We conducted a retrospective descriptive study of 23 pediatric patients diagnosed with and managed for lung abscess in Jordan. Data collected included demographic characteristics, clinical presentation, laboratory findings, treatment regimens, and outcomes. Results The mean age was 7.2 years (SD 3.1), with 60.9% male and no underlying chronic diseases in any patient. Systemic symptoms such as fever (91%) and hypoactivity (91%) were common. Cough was reported in 87% of cases, with varying patterns (dry, wet, or both). Imaging confirmed that 56.5% of abscesses were located in the left lung and 43.5% in the right lung. TB was systematically excluded using PPD and PCR testing. All patients received initial broad-spectrum antibiotics; 87% required escalation to include piperacillin–tazobactam combined with aminoglycoside (either amikacin or gentamicin). The mean duration of antibiotic use was 4.8 weeks. Only one patient (4.3%) underwent surgical intervention, and two patients (8.7%) required ICU care. Follow-up imaging 1–2 weeks after completion of therapy showed full resolution in 91% of cases. Conclusions Pediatric lung abscess in otherwise healthy children presents with significant systemic and respiratory symptoms but responds well to prolonged, escalated antibiotic therapy. Conservative management is effective in the majority of cases, with excellent clinical and radiological outcomes and low surgical intervention rates.